Broadband receiver of narrowband signal based on the cascaded stochastic resonance - Cheng-guo HOU; Bo-wen LUO; Di LI (Tongxin xuebao)
To improve the demodulation gain of traditional narrowband receiver,a narrowband signal receiving method of broadband based on cascaded stochastic resonance is proposed.On one hand,the noise in the signal is converted to the signal energy by the stochastic resonance operation on the received signal.On the other hand,by cascading stochastic resonance systems,the received signal is changed into square wave signal; and by constructing related sequences with prior information of received signal,the demodulation output has high gain.Theoretical analysis and simulation results show that compared with the traditional approach,this method improves detection performance in terms of SNR by more than 3 dB.And for receiving SNR of QPSK in −7～1 dB,the gain increased is about 20 dB.